TYPES AND TECHNIQUES OF HANDLOOM SAREES IN MUBARAKPUR (AZAMGARH DISTRICT) - Yadav, Priyanka; Gupta, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is known for its diversified art and cultural history. In which textile art occupies a prominent place. Clothing is one of the basic needs of human beings. Day by day different types of textiles and new types of weaving techniques are being used. All over the world, handloom is playing an important role in fulfilling these needs of people. Handloom is very labor-intensive work. After the agriculture sector, the textile industry provides direct and indirect employment to millions of people. An attempt is made to show all these aspects through this research paper, the history of handlooms in Mubarakpur, the sarees, their technology, and the challenges faced by the weavers at present. This paper discusses the weaving tradition of Mubarakpur, especially the sarees made here. Mubarakpur, which is called the city of silk, is the weavers of Mubarakpur transferring their unique weaving art from one generation to the next, keeping their traditions. This research is investigating the history of handloom in Mubarakpur, and the present condition of the clothes made there. To highlight the changes taking place. What types of sarees are made in Mubarakpur? The main objective of this research paper is to investigate their technology and what types of problems weavers are facing. Skilled weavers and people of the Mubarakpur were selected for this study. In which there are both men and women. Questionnaire methods and personal interviews have been used to collect information